Stress experienced by mothers of neonates in a private hospital NICU. - Buys, Lauren Mildred (My University, 2014)
Mothers of neonates admitted to neonatal intensive care units appear to suffer stress which may be related to the illness and treatments the neonate is undergoing, separation from the neonate and social and relationship issues. Nursing professionals employed in the neonatal intensive care unit (NICU) need specific preparation in order to assist mothers to cope with the experience of their neonate being admitted to the NICU. Research is required in order to adequately describe the nature of the stress and whether it changes over a period of time and to provide nursing professionals with information relating to the subject of stress suffered by mothers in this situation. A quantitative, longitudinal study of stress experienced by mothers of the neonate NICU patient was undertaken using the Neonatal Unit Parental Stress (NUPS) Scale (Reid, Bramwell, Booth & Weindling, 2007) (Reid et al., 2007). Mothers who met inclusion criteria were recruited to participate in the study. They were asked to complete the NUPS questionnaire at two time points. Correlations were examined between data obtained on the NUPS questionnaire and the mother and infant demographic data. The results of this study have shown that mothers experience the greatest stress as a result of neonatal suffering and their inability to perform functions of the mother role as a result of separation from the neonate. These findings have been used to make recommendations for the preparation of nursing professionals who work in the NICU.
Keywords: Neonatal Nursing; Maternal-Child Nursing